Arrhythmogenic right ventricular cardiomyopathy: severe structural alterations are associated with inflammation. Issue 12 (3rd September 2012) - Campuzano, Oscar; Alcalde, Mireia; Iglesias, Anna; Barahona-Dussault, Catherine; Sarquella-Brugada, Georgia; Benito, Begoña; Arzamendi, Dabit; Flores, Jose; Leung, Tack Ki; Talajic, Mario; Oliva, Antonio; Brugada, Ramon
Abstract : Aim: Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) is a rare cardiomyopathy associated with sudden cardiac death. It is characterised by a progressive right ventricle (RV) fibrofatty replacement, although biventricular replacement (BV) is also common. Inflammation believed to be a key player in disease progression and outcome. Our study investigates the relationship between the presence of inflammatory infiltrates in myocardium and the severity of structural heart alterations in ARVC. Methods: Our study included eight control and 36 ARVC postmortem human heart samples. We performed macroscopic assessment and microscopic analysis for different inflammatory cell types. Results: Fibrofatty replacement of RV was present in all our cases. Thirteen cases showed sole RV involvement (36.11%). Of these, only one showed inflammatory infiltrates (7.69%). Sixteen cases showed severe ARVC phenotypic forms characterised by BV involvement and right auricular (RA) fatty accumulation plus RV dilation (44.44%); eight of them also showed inflammatory infiltrates (50%). Immunohistochemical studies revealed ventricular multifocal inflammatory infiltrates, showing seven T-lymphocytes as the main infiltrate cell types. Conclusions: The presence of inflammatory infiltrates in ventricular myocardium of ARVC samples is associated with severe structural heart changes, indicating that an inflammatory process may be a modulator of severity in ARVC.